Prevalence of infectious diseases among Mongolian blood donors - Boldtsetseg Tserenpuntsag; Lamjav Ouynbileg; Kenrad Nelson; Louise-Anne McNutt (Journal of Infection in Developing Countries)
Objectives: This study estimates the prevalence of screened infections: human immunodeficiency (HIV), hepatitis B (HBV) virus, hepatitis C (HCV) virus, brucellosis, and syphilis among Mongolian blood donors. Methods: This report is based on routine data collected from simple questionnaires completed by a sample of consecutive donors visiting the Blood Center between August 2004 and February 2005. Results: Seropositivity rates were as follows: HIV 0%, HBsAg 8.1% (n=185), anti-HCV 8.7% (n=195), brucellosis 3.3% (n=75), and syphilis 2% (n=44). HBsAg seropositivity was concentrated among young donors less than 20 years of age (P